Entrance gateway of the Bhandasar Temple - Temples of India Project Team (Jio Institute, 2024)
The foliated archway with fluted pilaster column motifs on either side leads into the temple. Beyond the archway are two transepts puncturing the inner walls of the entrance gateway.